Prevalence, pattern and perceptions of self-medication in medical students - Pandya, Rushi N.; Jhaveri, Kunal S.; Vyas, Falgun I.; Patel, Varsha J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The use of self-medication is highly prevalent in the community more so amongst the medical students. Self-medication can be defined as the use of drugs to treat self-diagnosed disorders or symptoms, or the intermittent or continued use of a prescribed drug for chronic or recurrent disease or symptoms. Aims and Objectives: To study the prevalence and pattern of use of self-medication among medical students from first year to internship. Methods: This cross sectional study was carried out among under graduate medical students including interns of Smt. NHL Municipal Medical College, Ahmedabad during the period of March 2010 to May 2010. Results: Out of 747 students and interns enrolled, 685 responded (91.7%). Out of 685 respondents 564 (82.3%) reported self-medication within one year of recall period. Most common conditions/symptoms for self-medication in students were fever (72.7%), headache (69.1%), upper respiratory tract infections (64.1%) followed by others like body-ache, abdominal pain, diarrhoea etc. Over the counter drugs (84.2%) was the most common category of drugs used by all the students except first year students who used prescription only drugs more frequently (48.5%). Herbal and Ayurvedic drugs were also used as self-medication (17.8%); most frequently by the first year students (22.7%). Conclusion: The pattern of self-medication practice changes with time and advancement of knowledge.